2013
DOI: 10.1007/s10633-013-9400-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-adapting light intensity on dark adaptation in early age-related macular degeneration

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent AbstractBackground: This study aimed to identify the pre-adapting light intensity that generated the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Brown, Adams, Coletta, and Haegerstrom-Portnoy (1986) found decreased sensitivity for both rods and cones, as well as increased time constant for rod-recovery during dark adaptation in early AMD. Recent studies have provided evidence for AMD related increases in the time constant for cone recovery (Gaffney, Binns, & Margrain, 2011; Gaffney, Binns, & Margrain, 2013), delayed rod-cone break (Dimitrov, Guymer, Zele, Anderson, & Vingrys, 2008; Gaffney et al, 2011; Gaffney et al, 2013; Owsley, Jackson, White, Feist, & Edwards, 2001), and delayed rod recovery (Brown et al, 1986; Dimitrov et al, 2008; Dimitrov et al, 2011; Owsley et al, 2001). Impaired dark adaptation has been found in different retinal locations (Gaffney et al, 2011; Steinmetz, Haimovici, Jubb, Fitzke, & Bird, 1993) and at different bleach levels (Dimitrov et al, 2008; Gaffney et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Brown, Adams, Coletta, and Haegerstrom-Portnoy (1986) found decreased sensitivity for both rods and cones, as well as increased time constant for rod-recovery during dark adaptation in early AMD. Recent studies have provided evidence for AMD related increases in the time constant for cone recovery (Gaffney, Binns, & Margrain, 2011; Gaffney, Binns, & Margrain, 2013), delayed rod-cone break (Dimitrov, Guymer, Zele, Anderson, & Vingrys, 2008; Gaffney et al, 2011; Gaffney et al, 2013; Owsley, Jackson, White, Feist, & Edwards, 2001), and delayed rod recovery (Brown et al, 1986; Dimitrov et al, 2008; Dimitrov et al, 2011; Owsley et al, 2001). Impaired dark adaptation has been found in different retinal locations (Gaffney et al, 2011; Steinmetz, Haimovici, Jubb, Fitzke, & Bird, 1993) and at different bleach levels (Dimitrov et al, 2008; Gaffney et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that deficits in rod-mediated retinal function occur as a natural consequence of normal aging [ 36 , 49 , 50 , 51 , 52 ] a process that may be accelerated in age-related macular degeneration (AMD) [ 34 , 38 , 39 , 49 , 53 , 54 , 55 , 56 ]. There are numerous psychophysical studies that have demonstrated decreases in rod-mediated sensitivity and prolonged dark-adaptation kinetics even in early AMD [ 33 , 34 , 36 , 38 , 39 , 54 , 55 , 56 , 57 , 58 , 59 ]. Thus, many have proposed scotopic thresholds as a potential endophenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Dimitrov et al [15,41] assessed using both techniques. Eight studies used an adapted Humphrey Visual Field Perimeter (HVFP; Carl Zeiss Meditec, Inc, Dublin, CA, USA) [43][44][45][46][47][48][49][50] and eight utilised an 'in-house' adaptometer, with methods developed by investigators [15,41,42,[61][62][63][64][65]. Other adaptometers, featured in more than one study, included the Medmont Dark Adapted Chromatic perimeter (MDAC; Medmont Pty Ltd, Melbourne, Australia) (5 out of 27 studies) [55][56][57][58][59] and the Macular Disease Detection MDD-2 Ò device (Health Research Science, LLC, Lighthouse Pt, FL, USA) (2 out of 27 studies) [53,54].…”
Section: Other Adaptometers and Photostress Testsmentioning
confidence: 99%
“…The most frequently reported parameters of DA in studies that did not use the AdaptDx were RCB (10 out of 27 studies) [41, 42, 44-48, 60, 63, 65], cone absolute threshold (9 out of 27 studies) [41, 42, 44-48, 63, 65], cone time constant (8 out of 27 studies) [44][45][46][47][48][49][50]65] and RIT/ rod criterion time (7 out of 27 studies) [41,[55][56][57][58][59]63]. Other parameters in the reviewed papers included rod absolute threshold (5 out of 27 studies) [41,[46][47][48]63] and 'second slope' or rod slope (5 out of 27 studies) [42,[46][47][48]65], which refers to the second phase of rod recovery when threshold data are fitted with a model based on the physiological process of DA [7].…”
Section: Other Adaptometers and Photostress Testsmentioning
confidence: 99%